Against the odds: Network and institutional pathways enabling agricultural diversification - Blesh, Jennifer; Mehrabi, Zia; Wittman, Hannah; Bezner Kerr, Rachel; James, Dana; Madsen, Sidney; Smith, Olivia M.; Snapp, Sieglinde S.; Stratton, Anne Elise; Bakarr, Abram J.; Bicksler, Mohamed; Galt, Ryan; et al. (Elsevier, 2023)
Farming systems that support locally diverse agricultural production and high levels of biodiversity are in rapid decline, despite evidence of their benefits for climate, environmental health, and food security. Yet, agricultural policies, financial incentives, and market concentration increasingly constrain the viability of diversified farming systems. Here, we present a conceptual framework to identify novel processes that promote the emergence and sustainability of diversified farming systems, using three real-world examples where farming communities have found pathways to diversification despite major structural constraints. By applying our framework to analyze these bright spots in the United States, Brazil, and Malawi, we identify two distinct pathways—network and institutional—to diversification. These pathways emerge through alignment of factors related to social and ecological structure (policies, institutions, and environmental conditions) and agency (values, collective action, and management decisions). We find that, when network and institutional pathways operate in tandem, the potential to scale up diversification across farms and landscapes increases substantially.